Spectral analysis of acoustic emission signals generated by twinning and shear band formation in silver single crystals subjected to channel-die compression tests - Ranachowski, Zbigniew; Piątkowski, A.; Pawełek, A.; Jasieński, Z. (Archives of Acoustics, 2006)
In the paper there are presented the results of investigations of the relations between acousticemission (AE) and the mechanisms of twinning as well as shear band formation and propagationin silver single crystals of $\{112\}$ orientation, subjected to channel-die compressiontests at ambient temperature. The results were obtained using an AE analyzer of a newgeneration, installed recently at the Institute of Metallurgy and Materials Sciences, and werecompared with those obtained also for single Ag crystals of the same orientation, tested at theroom and at liquid nitrogen (−196$^{°}$C) temperatures, but registered applying an AE analyzerof older generation, used until now. The results of AE measurements obtained using the newanalyzer allowed to plot the acoustograms produced with the application ofWindowed FourierTransform method for analysis of large experimental data sets (4$×$132 Msamples). This allowedthe authors to solve the problem of identification of the strain mechanisms leading toformation of different dislocation systems.